The data visualization workshop : an interactive approach to learning data visualization - Döbler, Mario; Grössmann, Tim (Packt Publishing Ltd, 2020)
The Data Visualization Workshop focuses on building up your practical skills so that you can develop clear, expressive real-world charts and diagrams. You'll learn from real examples that lead to real results with Python.